2021
DOI: 10.7554/elife.60270
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-specific opioid receptor signaling is selectively modulated by different dynorphin peptides

Abstract: Many signal transduction systems have an apparent redundancy built into them, where multiple physiological agonists activate the same receptors. Whether this is true redundancy, or whether this provides an as-yet unrecognized specificity in downstream signaling, is not well understood. We address this question using the kappa opioid receptor (KOR), a physiologically relevant G protein-coupled receptor (GPCR) that is activated by multiple members of the Dynorphin family of opioid peptides. We show that two rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…SpH fluorescence is quenched inside the acidic intracellular compartments (pH = 4.5–6.5) but exerts high fluorescence once it is inserted into the plasma membrane and exposed to the neutral extracellular environment (pH = 7.4; Fig. 1 A ; Voglmaier et al, 2006 ; Yudowski et al, 2006 , 2009 ; Puthenveedu et al, 2010 ; Vistein and Puthenveedu, 2013 ; Kunselman et al, 2019 , 2021a ; Chanaday and Kavalali, 2021 ). This change in fluorescence can be visualized under TIR-FM where only fluorophores within 100 nm of the plasma membrane are excited ( Axelrod, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SpH fluorescence is quenched inside the acidic intracellular compartments (pH = 4.5–6.5) but exerts high fluorescence once it is inserted into the plasma membrane and exposed to the neutral extracellular environment (pH = 7.4; Fig. 1 A ; Voglmaier et al, 2006 ; Yudowski et al, 2006 , 2009 ; Puthenveedu et al, 2010 ; Vistein and Puthenveedu, 2013 ; Kunselman et al, 2019 , 2021a ; Chanaday and Kavalali, 2021 ). This change in fluorescence can be visualized under TIR-FM where only fluorophores within 100 nm of the plasma membrane are excited ( Axelrod, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…1, B, D, and F ). We and others have extensively characterized these puffs previously as individual vesicle fusion events mediating recycling of receptors from endosomes, by showing that GPCR puffs are rarely observed without prior agonist-mediated internalization of the receptors, that mutation of receptor sequences that are required for B2AR and MOR recycling abolishes the puffs, that pharmacological treatments that increase or decrease recycling cause a corresponding change in puffs, and that cycloheximide (CHX) treatment does not significantly reduce the number of puffs ( Yudowski et al, 2006 ; 2009 ; Puthenveedu et al, 2010 ; Vistein and Puthenveedu, 2013 ; Sposini et al, 2017 ; Kunselman et al, 2019 , 2021a ).…”
Section: Resultsmentioning
confidence: 99%
“…The physiological outcome of activating a receptor is the integrated response of these multiple phases of signaling, separated by time and space (31,32). Gi-coupled receptors, such as opioid receptors, can also be in active conformations on endosomes after ligand-dependent activation at the PM (21,33). For these known examples, because the ligand is extracellular, mechanisms exist to transport the ligand to the endosomes, either by transporters that allow movement of small ligands such as catecholamines across the membranes, or by trafficking mechanisms that internalize larger ligands such as peptides (21,32).…”
Section: Discussionmentioning
confidence: 99%
“…ORs are the targets of endogenous neuromodulatory neuropeptides and of therapeutically important analgesic opioid drugs, such as morphine and fentanyl. Nanobody-based sensors recently revealed that mu- (MOR), delta- (DOR), and kappa- (KOR) ORs undergo ligand-dependent activation not only in the PM but also in different cellular organelles, including endosomes and the Golgi apparatus ( 7 , 9 , 10 ). Opioid neuropeptides and opioid drugs notably differ in their subcellular activation patterns in that small-molecule drugs uniquely trigger activation of ORs in the Golgi apparatus ( 7 ).…”
Section: Introductionmentioning
confidence: 99%